Do large shareholders separate the roles of CEO and board chairman for expropriations? Evidence from pyramidal business groups in China. Issue 3 (4th May 2021) - Liu, Huilong; Qi, Yunfei; Wang, Hong
ABSTRACT: This paper proposes that the separation of the roles of CEO and board chairman is a result of, rather than a solution to large shareholder agency problem. We support this view by examining the probabilities of CEO duality in pyramidal groups. We find that the probability of CEO duality is negatively associated with the number of pyramid layers and large shareholder expropriation, the number of pyramid layers and the level of large shareholder expropriation are positively related. Further analysis reveals that CEO duality improves (dampens) firm performance in cases of more (fewer) pyramid layers.